Dinamika Kemiskinan di Aceh: Analisis PDRB, Pengangguran dan Indeks Pembangunan Manusia - Miswar Miswar; Siti Maysarah; Maryana Maryana; Musrizal Musrizal; Roza Mahardika; Nurmaliza Nurmaliza; Cut Sofia Ramadina (Sekolah Tinggi Ilmu Administrasi Nasional, 2023)
Even though some developing nations have successfully implemented production and national income development, poverty in these countries remains a very complex issue. This study investigates the concurrent and partial effects of the Gross Regional Domestic Product, Unemployment, and the human development index on poverty in Aceh Province. The data used in this study is secondary data based on time series available on the official website of the Aceh Provincial Statistics Center for the 2017–2022 period. The processing of this research data uses the E-Views 10.0 program. The research analysis employed in this study is a panel or regression analysis, which indicates that the variables GRDP, unemployment, and HDI are the independent variables, and poverty is the dependent variable. GRDP partially has a positive and significant effect on poverty. Unemployment has a partial and insignificant effect on poverty. HDI partially harms poverty. Simultaneously, it concludes that the Gross Regional Domestic Product, Unemployment, and the Human Development Index significantly affected poverty.